A Project feasibility study on a study center - Alcaraz, Eunice A. (College of Engineering, 1993)
The establishment of a Study Center located within the U.P. Diliman Campus has a large potential market and is technically and economically feasible. It has the following characteristics: (1) The Study Center is a place where students may study individually, have group discussions, or work on computers from 6 p.m. to 6 a.m., Mondays to Saturdays. (2) The Study Center will be located in the rear building of the Transport Training Center, Magsaysay St., UP Diliman (in front of Yakal Residence Hall and very near Molave Residence Hall). (3) Offers the following services: individual study area, discussion are and computer rental. (4) The amenities are the following: well lighted working areas, well ventilated rooms, clean comfort rooms and security.